PENGARUH QUALITY OF WORK LIFE (QWL) DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS GURU SD SWASTA KATOLIK DI JAKARTA PUSAT - Lucia Klamensia Rahaded (Universitas Negeri Jakarta, 2017)
The objective of this research was to understand the effect of Quality Of Work Life (QWL) and organizational culture on productivity. It was a quantitative research was conducted ten schools located in Jakarta Centre.The research uses a survey method with path analysis was applied in testing hypothesis. It was conducted to 153 teachers at Private Catholic Elementary Schools as the respondents which were selected in a simple random way.The result of this study are: (1). There is a positive direct effect of Quality Of Work Life (QWL) on productivity. (2). There is a positive direct effect of organizational culture on productivity, and (3). There is a positive direct effect of Quality Of Work Life (QWL) on organizational culture.